Study of relationship marketing towards the customer retention practices by HICOM Diecasting Sdn Bhd / Khairun Aini Roslan - Roslan, Khairun Aini (Faculty of Business and Management, 2009)
The purpose of study is to define study of relationship marketing towards customer retention practices by HICOM Diecasting. The collection of information gathered from the secondary data trough the journals local, interview and observation. From the study, researcher identified three factors arises is customer loyalty, customer satisfaction, and services quality to implement the marketing strategy and the competitive advantage of this company. Conclusion, researcher gives some suggestion on improvement in their customer satisfaction survey and implement in the future.